Clinical Implications of Hematologic and Hemostatic Abnormalities in Children With COVID-19. Issue 1 (27th April 2021) - Leeman, Rachel; Shoag, Jamie; Borchetta, Michael; Mitchell, Charles; Davis, Joanna A.; Corrales-Medina, Fernando F.
Abstract : Leukopenia, thrombocytopenia, elevated D-dimer, and prolonged prothrombin time are considered poor prognostic factors in adults with acute Coronavirus Disease 2019. The prognostic significance of these abnormalities among pediatric patients remains underreported in the literature. This retrospective cohort study evaluates the prognostic implications of hematologic and hemostatic derangements in patients younger than 22-years-of-age who were admitted to a tertiary-care referral institution for management of acute Coronavirus Disease 2019 infection. Leukopenia and thrombocytopenia were identified as independent prognostic factors of disease severity. Although the majority of children, with available results, had elevated D-dimer or prolonged prothrombin time upon initial presentation, these markers were not found to be associated with the development of severe clinical complications.